The painting impressions in the creativity of Oleksandr Oles and European symbolists - Цуркан, Ігор Миколайович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The creativity of Oleksandr Oles is marked by the influence of the romantic poetics, the most important component of which was the lyrical mood and the melodiousness of the phrases, that created the individual image of the spiritual being on the way to the beauty and dream.Oleksandr Oles brought the idea of the “inner individual”, who revolted against the world and the public and government norms. The originality of the system of the artistic images, motives, spirits, rhythm and melodic absorbed the powerful lyricism of the poets’ sensitive soul.That’s why the purpose of this article is the revelation the images, which creates the metaphorical universe, filled with symbols of the human existence. Obtaining the purpose envisages to investigate the system of symbols of Oleksandr Oles and European symbolists and to reveal its realization in the authors’ interpretations. The methods of the research is based on the main principles of the philological analysis of the text. The determined tasks foresee the use of elements of comparative and hermeneutic analysis as a general interpretation of literary texts.